2018
DOI: 10.1097/sla.0000000000003169
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Blood Flow in the Gastric Conduit With Thermal Imaging for Esophageal Reconstruction

Abstract: Objective: The study's primary aim was to evaluate the effectiveness of thermal imaging (TI) and its secondary aim was to compare TI and indocyanine green (ICG) fluorescence angiography, with respect to the evaluation of the viability of the gastric conduit. Summary Background Data: The optimal method for evaluating perfusion in the gastric conduit for esophageal reconstruction has not been established. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…However, all of those probe-based optical techniques provide a pin-point perfusion quantification with none or minimal spatial information, and this greatly limits their routine intraoperative use. In this view, technologies with a better spatial resolution, such as laser speckle [ 28 ], fluorescence angiography (FA) [ 6 ], or thermography [ 29 ] have been explored. However, in spite of interesting results, the laser speckle’s perfusion measurement is highly variable in relation to distance and angulation from the target, and the accuracy of this technology has not yet been validated in a controlled experimental setting, using reliable ischemia biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all of those probe-based optical techniques provide a pin-point perfusion quantification with none or minimal spatial information, and this greatly limits their routine intraoperative use. In this view, technologies with a better spatial resolution, such as laser speckle [ 28 ], fluorescence angiography (FA) [ 6 ], or thermography [ 29 ] have been explored. However, in spite of interesting results, the laser speckle’s perfusion measurement is highly variable in relation to distance and angulation from the target, and the accuracy of this technology has not yet been validated in a controlled experimental setting, using reliable ischemia biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…However, this metric is not yet universally accepted and larger trials are necessary to understand its real clinical usefulness. Nishikawa et al [ 29 ] have shown interesting results using thermal imaging during esophagectomies. In particular, the authors proposed a score based on the temperature and on the length of the gastric conduit and its supplying vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Both procedures enabled the construction of a carefully designed gastric conduit in which blood flow could be assessed with thermal imaging. They are therefore considered non‐traumatic procedures and may equally protect the stomach against surgical manipulation 20 …”
Section: Discussionmentioning
confidence: 99%
“…If we had been concerned about impaired blood flow through the gastric tube, we would have performed the reconstruction using the colon or small intestine. At the time the patient was treated, it was not possible to conduct blood flow assessments using indocyanine green or thermal imaging at our institution [22]. The initial non-surgical treatment almost closed the fistula, but the subsequent restarting of oral intake caused the fistula to worsen.…”
Section: Direct Approachmentioning
confidence: 99%